The Influence of Parasocial Relationship, Promotion, and Perceived Usefulness on Customer Loyalty in TikTok Livestream - Atik Zanzabila; Kurniawati Kurniawati; Renny Risqiani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The rapid growth of social media and e-commerce has positioned TikTok as a prominent platform for livestreaming commerce, with high user engagement in Indonesia. This study aims to examine the effects of parasocial relationship, promotion, and perceived usefulness on purchase behavior and customer satisfaction, and their implications for customer loyalty within the Stimulus–Organism–Response (SOR) framework. A quantitative approach was employed using purposive sampling, involving 308 active TikTok users aged 18 years and above who had watched and purchased through TikTok livestreams. Data were collected via an online questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS Software. The findings reveal that parasocial relationship significantly influence purchase behavior, while purchase behavior and customer satisfaction have significant positive effects on customer loyalty. Promotion significantly affects customer satisfaction, whereas perceived usefulness does not.